Pengetahuan, Sikap dan Perilaku Pencegahan Penularan COVID-19 - Ulfa Husnul Fata; Hipolito Da Cruz Soares (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the knowledge, attitudes, and behavior of preventing the transmission of COVID-19. This research method is quantitative research with a descriptive design. The results showed that 28 (58.0%) knowledge about preventing COVID-19 transmission was in the excellent knowledge category, 28 (58.0%) attitudes about preventing COVID-19 transmission were in the superb attitude category, and behavior about 28 (58.0%) was included in the type of good behavior. Conclusions, knowledge, attitudes, and behavior regarding the prevention of COVID-19 transmission in Karang Rejo Village, Ringin Kembar Hamlet, RT 02 RW 09, are in the excellent category. Keywords: COVID-19, Knowledge, Behavior, Attitude